Digital Native Students’ Perspectives of Online Games Use for Learning Grammar in English Class at Avizena.Edu Private Course - Muhammad Rauuf Oktavian Nur; Yusiana Ardita; Brilliant Oliviera (Jurnal Studi Guru dan Pembelajaran, 2020)
As one of the important factors in learning language, learning grammar become a great topic to discuss and enhance. Digital native students who are common in use their devices in order to help them enhance their learning language, online games are unique media to apply in their language class. This study conducted at Avizena.edu private courses in Magelang, Central Java Province, Indonesia. High school students who were enrolled in the English class are our respondents. The survey conducted the following aspects: preferences, actual use, ease of use, experience, and learning opportunities. Digital native students were also invited to share potential positive and negative benefits for online game use in the classroom. A hundred students completed the survey. Results indicate that most students viewed the potential utilization and integration of online games as positive. Moreover, some digital native students expressed pertain that the use of language online games may not give an efficient or effective method and impact in learning grammar activities.